The potential and usefulness of demand response to provide electricity system services - Aryandoust, Arsam; Lilliestam, Johan (Applied Energy, 2017)
The expansion of fluctuating renewable electricity sources creates new challenges for grid operators. One often suggested solution is demand-side response (DR): the adaptation of electricity consumption to generation. Here, we investigate what role DR could play to support system stability through fully remote-controlled (by the grid operator) shifts of individual processes in households and in the commercial and industrial sectors, testing the case of a high-renewables future in Germany. The grid operator is constrained by consumer acceptance of service interruptions, both in size and shift duration, and by technical boundaries. We find that DR has a large potential and is suited for short-term services such as spinning reserve or primary control and for damping residual load gradients. However, its potential is low for longer-term services like secondary/tertiary control or for satisfying residual load during low sun/wind times in a high-renewables future. We find that the potential for DR is not limited by the magnitude of shiftable capacity but by the maximum shift duration and the patterns of switching between positive and negative power demand, which makes DR useful for fast and short-term services but less useful for longer shifts.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Demand-side management (DSM); Demand-side response (DR); Energy strategy 2030 & 2050; Operating reserves; Renewable power integration; System balancing